Pengembangan Model Pelatihan Untuk Meningkatkan Kompetensi Guru Dalam Pembelajaran Karakter dan Kecakapan Hidup (Studi Pada Sekolah Islam Baiturrahmah) - Nurnaeni, Neni; Komara, Endang; Andriani, Rian; Lutfiansyach, Dadang Yunus (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
This research aims to develop an effective training model to enhance teacher competency in character and life skills education at Baiturrahmah Character Islamic School. The research method used was a case study involving 10 teachers as respondents. Data were collected through classroom observations, interviews, and questionnaires. The results showed that the developed training model was effective in enhancing teacher competency in character and life skills education. After the training, teachers demonstrated an improved understanding of the importance of character and life skills education, as well as their ability to design and implement learning activities that promote student character development. Additionally, teachers reported positive changes in student attitudes and motivation, as well as improvements in their social and emotional skills. Teachers also provided positive feedback on the use of teaching methods and strategies gained from the training. It is expected that this training model can be adopted by other schools to enhance teacher competency in character and life skills education. Further research can be conducted to identify factors influencing the success of this training model and measure its impact on student achievements.